Psikologi Komunikasi dalam Meningkatkan Dakwah Da’i di Masjid Fajar Ikhlas Kelurahan Sumberejo Kecamatan Kemiling - Mutia Yanti, Yunidar Cut (AL-ADYAN, 2017)
Communication psychology explains about how to communicate well by taking a psychiatric approach to his mad'u. Because by mastering the psychology of communication, a preacher can adjust the material and the way the delivery of preaching to his madam. So that an effective da'wah can occur. For this, a preacher must use the science of communication psychology in order to be able to understand the state or psychology of his mad'u. Because basically a person's psyche is different, therefore it takes a way to communicate or convey messages in different ways. So an effective da'wah will occur. The research method used is field research (research that is conducted directly in the field or the respondent. The population and sample in this study are the preachers and members of the Ikhlas Fajar Council. From the results of this study it can be seen that the Da'i at the Fajar Ikhlas Mosque, the Da'i have not fully used the science of Communication Psychology, therefore the preaching it delivered was less effective.